2020
DOI: 10.1371/journal.pone.0227051
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk factors and impact of cyberbullying victimization among university students in Myanmar: A cross-sectional study

Abstract: Background Cyberbullying is a global public health concern with tremendous negative impacts, not only on the physical and mental health of students but also on their well-being and academic performance. However, there are very few studies on cyberbullying among university students, especially in Myanmar. This study aims to determine the percentage of university students who suffered cyberbullying victimization in the last 12 months, and the association between students' socio-demographic characteristics, adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 40 publications
(140 reference statements)
3
33
1
10
Order By: Relevance
“…A second search, using the identical article selection and data collection processes, was conducted in July 2020 to determine whether there were any recently published papers of relevance. Five additional papers [53][54][55][56][57] were added, bringing the total number to 43 articles.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second search, using the identical article selection and data collection processes, was conducted in July 2020 to determine whether there were any recently published papers of relevance. Five additional papers [53][54][55][56][57] were added, bringing the total number to 43 articles.…”
Section: Study Selectionmentioning
confidence: 99%
“…When victimisation occurred within an office or university/college environment, adults explained they felt a desire to leave their job (with some actually quitting 26,27,51 ), it affected their work 26 or school assignments 30 , and found it harder to understand lectures than usual 53 . One student explained cyberbullying caused her to stop playing softball in her senior year at school, which she believes resulted in her losing a chance for a college scholarship 25 .…”
Section: Impact Of Cyber Victimisationmentioning
confidence: 99%
“…As university students become “digital natives” [ 61 ], they become sophisticated users of technology, but are also exposed to a host of additional risks, including cyberbullying [ 62university ]. Cyberbullying among university students influences their academic, social, and emotional development [ 63 , 64 , 65 ], and is associated with difficulties in concentration and substance abuse [ 66 ].…”
Section: Overview Of Cyberbullyingmentioning
confidence: 99%
“…There is growing evidence that cyberbullying can be a catalyst for impaired mental health, psychological distress, fear, and increased risk of suicide [ 68 ]. Moreover, student victims of cyberbullying report depression, loneliness, interpersonal and family problems, maternal attachment anxiety, low self-esteem, substance abuse, and suicidal ideation, all of which affect their personal and professional lives and mental health [ 60 , 65 , 66 , 69 , 70 ]. Additionally, a study by Felipe-Castaño et al.…”
Section: Overview Of Cyberbullyingmentioning
confidence: 99%
“…Except for psychological damage, cyberbullying may have more terrible impacts. Although the network and reality are far apart, some of the more serious cases of cyberbullying can turn into actual violence when they think they cannot solve their conflicts on the Internet [ 7 , 8 ]. Studies have found that cyberbullying was positively correlated with actual bullying, which means that those who bullied others online were also more likely to bully others in real life, and vice versa [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%